Tinjauan Kondisi Fisik Atlet Bola Basket - Pranata, Randa; -, Umar; Sin, Tjung Hauw; Oktavianus, Irfan (Jurnal Gladiator, 2022)
The problem in this study is that it has been almost 6 years since the club was formed, but in terms of achievement, it can be categorized as sedentary or even declining. Researchers suspect that the low level of achievement is due to the low level of the athlete's physical condition. This study aims to determine the level of physical condition of the basketball athletes Ocean Generation Club Padang City. This type of research is descriptive. The research was conducted in January 2021. The population in this study were 17 basketball clubs Ocean Generation Club Padang City. The sampling technique was purposive sampling, consisting of 10 male athletes. The instruments in this study were: 1) 50 Meter Run, 2) Shuttle Run, 3) Vertical Jump, 4) Two Hand Medicine Ball Putt Test, 5) bleep Test, 6) bridge-Up Test. The data analysis technique used in this study is the frequency distribution. The results showed that: 1) The speed level of the athlete was in the moderate category with an average of 7.13, 2) The level of the athlete's agility was in the less category with an average of 17.66, 3) The level of the athlete's limb muscles was in the category of less than average. -average 50.9, 4) The level of explosive power of the athlete's arm muscles is in the good category with an average of 5.57, 5) The level of aerobic endurance of the athletes is in the good category with an average of 43.21, 6) The level of flexibility of the athletes is at category enough with an average of 64.9